Graves' Disease and Treatment Effects on Warfarin Anticoagulation. (4th June 2014) - Howard-Thompson, Amanda; Luckey, Alexis; George, Christa; Choby, Beth A.; Self, Timothy H.
Abstract : Background . Hyperthyroidism causes an increased hypoprothrombinemic response to warfarin anticoagulation. Previous studies have demonstrated that patients with hyperthyroidism require lower dosages of warfarin to achieve a therapeutic effect. As hyperthyroidism is treated and euthyroidism is approached, patients may require increasing warfarin dosages to maintain appropriate anticoagulation. We describe a patient's varying response to warfarin during treatment of Graves' disease. Case Presentation . A 48-year-old African American female presented to the emergency room with tachycardia, new onset bilateral lower extremity edema, gradual weight loss, palpable goiter, and generalized sweating over the prior 4 months. She was admitted with Graves' disease and new onset atrial fibrillation. Primary stroke prophylaxis was started using warfarin; the patient developed a markedly supratherapeutic INR likely due to hyperthyroidism. After starting methimazole, her free thyroxine approached euthyroid levels and the INR became subtherapeutic. She remained subtherapeutic over several months despite steadily increasing dosages of warfarin. Immediately following thyroid radioablation and discontinuation of methimazole, the patient's warfarin dose and INR stabilized. Conclusion . Clinicians should expect an increased response to warfarin in patients with hyperthyroidism and close monitoring of the INR is imperative to prevent adverse effects. As patients approach euthyroidism, insufficient anticoagulation is likely without vigilant follow-up, INR monitoring, and increasing warfarin dosages.